2019
DOI: 10.20546/ijcmas.2019.802.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manuring Techniques on Soil Health, Yield and Economics of Maize–Wheat Cropping System under UKP Command

Abstract: Rice -Rice is the predominant cropping system being adopted by the farmers' long back in upper krishna and tunga bhadra projects being the largest irrigation projects in Karnataka. At present, the system being practiced is creating lot of problems with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…This clearly indicated that Sesbania aculeata have positive influence on rice grain yield when grown as intercrop for brown manuring than without Sesbania aculeata. The results are in conformity with the findings of Hiremath et al (2019). Kumar and Ladha (2010) reported that 10% lower yield in DSR compared to TPR in India.…”
Section: Rice Yield and Yield Componentssupporting
confidence: 91%
“…This clearly indicated that Sesbania aculeata have positive influence on rice grain yield when grown as intercrop for brown manuring than without Sesbania aculeata. The results are in conformity with the findings of Hiremath et al (2019). Kumar and Ladha (2010) reported that 10% lower yield in DSR compared to TPR in India.…”
Section: Rice Yield and Yield Componentssupporting
confidence: 91%